Food restriction for the prevention of ascites syndrome in broilers - Huera Ordoñez, Danny Stiven; Campos Vallejo, Rolando Martin; Ibarra Rosero, Edison Marcelo (Tierra Infinita, 2021)
The present investigation was developed in the Tulcán canton of Carchi province, which is located at an altitude of 2950 m.a.s.l., in order to evaluate feeding strategies for the control of ascites in broilers. The feeding strategies evaluated were T1 = no food restriction, T2 = 2 hours of food restriction*day-1, T3 = 4 hours of food restriction*day-1, and T4 = 6 hours of food restriction*day-1. In the experiment, 108 one-day-old chickens were used, which were distributed in 12 experimental units made up of 9 birds, under a randomized complete block experimental design. The experiment started from 15 days of age of the birds where the weight gain, feed conversión and mortality associated with the ascitic syndrome were evaluated. The information analysis was carried out using analysis of variance (ANAVA) and Tukey’s test at 5%. Statistical differences were not obtained for weight gain, but for food conversion and mortality associated with ascites, where the best treatments were those that had food restriction (T2, T3 and T4), being able to conclude throug